Effects of Various Flavonoids on the α-Synuclein Fibrillation Process - Xiaoyun Meng; Larissa A. Munishkina; Anthony L. Fink; Vladimir N. Uversky (Parkinson's Disease)
α-Synuclein aggregation and fibrillation are closely associated with the formation of Lewy bodies in neurons and are implicated in the causative pathogenesis of Parkinson's disease and other synucleinopathies. Currently, there is no approved therapeutic agent directed toward preventing the protein aggregation, which has been recently shown to have a key role in the cytotoxic nature of amyloidogenic proteins. Flavonoids, known as plant pigments, belong to a broad family of polyphenolic compounds. Over 4,000 flavonoids have been identified from various plants and foodstuffs derived from plants and have been demonstrated as potential neuroprotective agents. In this study 48 flavonoids belonging to several classes with structures differing in the position of double bonds and ring substituents were tested for their ability to inhibit the fibrillation of α-synuclein in vitro. A variety of flavonoids inhibited α-synuclein fibrillation, and most of the strong inhibitory flavonoids were also found to disaggregate preformed fibrils.